The Effect of Income Diversification and Land Ownership on the Welfare of Simalungun Coffee Farmers - Tirtana, Muhammad Arief; Sembiring, Sya’ad Afifuddin; Pratomo, Wahyu Ario (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study was to determine the effect of income diversification and land tenure on the welfare of Simalungun coffee farmers. This study used a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, data were collected through questionnaires from 100 coffee farmers in Simalungun Regency during 2024.12 - 2025.2. The results showed that income diversification had a positive and significant effect on coffee farmers' income, but not on welfare. On the other hand, land tenure had a positive and significant effect on income and welfare. These findings indicate that larger and more stable land tenure can increase farmers' income and improve welfare, while income diversification is only effective in increasing income but not enough to significantly improve welfare.